2011
DOI: 10.1002/hipo.20767
|View full text |Cite
|
Sign up to set email alerts
|

Lactational zinc deficiency‐induced hippocampal neuronal apoptosis by a BDNF‐independent TrkB signaling pathway

Abstract: It is well-known that zinc deficiency leads to neuronal death in the brain. Here we tested the hypothesis that changes in the TrkB signaling pathway are involved in hippocampal neuronal apoptosis of suckling offspring with maternal zinc deficiency. Postpartum mice were fed a zinc-deficient (0.85 ppm) diet and their offspring were used as a lactational zinc deficiency mouse model. At P7, P14, and P21, changes in hippocampal neuronal apoptosis were assessed by Nissl and TUNEL staining. BDNF levels and TrkB neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Furthermore, zinc also functions as an agonist for TrkB and potentiates LTP of CA3 synapses in hippocampal mossy fibers (134). Concerning cell survival, it has been reported that increased apoptotic cell death in hippocampal regions (including CA1, CA3, and dentate gyrus) and decreased phosphorylation of hippocampal TrkB and ERK were observed in lactating zinc deficient (0.85 ppm) mice (135). Importantly, a zinc deficient diet (0.2 and 1 ppm) for 3 and 6 weeks caused depressive and anxiety-like behaviors in addition to anhedonia (136138), while these depressive-like behaviors were reversed after chronic treatment with typical antidepressants (such as fluoxetine, imipramine, and reboxetine) (136, 138).…”
Section: Action Of Zinc In Depressionmentioning
confidence: 99%
“…Furthermore, zinc also functions as an agonist for TrkB and potentiates LTP of CA3 synapses in hippocampal mossy fibers (134). Concerning cell survival, it has been reported that increased apoptotic cell death in hippocampal regions (including CA1, CA3, and dentate gyrus) and decreased phosphorylation of hippocampal TrkB and ERK were observed in lactating zinc deficient (0.85 ppm) mice (135). Importantly, a zinc deficient diet (0.2 and 1 ppm) for 3 and 6 weeks caused depressive and anxiety-like behaviors in addition to anhedonia (136138), while these depressive-like behaviors were reversed after chronic treatment with typical antidepressants (such as fluoxetine, imipramine, and reboxetine) (136, 138).…”
Section: Action Of Zinc In Depressionmentioning
confidence: 99%
“…Severe zinc deficiency imposed to adult rats or mice decreases neural progenitor cell proliferation in the dentate gyrus of the hippocampus (Corniola et al 2008; Suh et al 2009). Severe zinc deficiency both during lactation and during adulthood has been shown to increase hippocampal apoptosis (Gao et al 2009; Xu et al 2011). Culture in zinc deficient media decreases the proliferation of IMR-32 neuroblastoma cells, causing an arrest of the cell cycle at the G0/G1 phase and the induction of apoptosis (Adamo et al 2010).…”
Section: Zinc and Brain Developmentmentioning
confidence: 99%
“…In fact, the independent actions of Src and BDNF have been reported in the past as a response to a dietary imbalance caused by zinc deficiency [88].…”
Section: Discussionmentioning
confidence: 99%